2020
DOI: 10.21203/rs.3.rs-47908/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

General Practitioners’ Experiences of Emergency Care and Treatment Planning in England: A Focus Group Study

Abstract: BackgroundEmergency Care and Treatment Plans are recommended for all primary care patients in the United Kingdom who are expected to experience deterioration of their health. The Recommended Summary Plan for Emergency Care and Treatment (ReSPECT) was developed to integrate resuscitation decisions with discussions about wider goals of care. It summarises treatment recommendations discussed and agreed between patients and their clinicians for a future emergency situation and was designed to meet the needs of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Similarly, we have previously reported that GPs view ReSPECT conversations as ongoing and processual. 19 However, excepting one doctor who encouraged the patient to take her time, the participating doctors aimed at completing the decision-making process in one conversation, timing conversations according to clinical urgency. In our earlier work on the full range of ReSPECT conversations – from those planned but not conducted, to those carried out to completion – we described how time constraints, coupled with clinical prompts such as a patient’s projected deterioration, influence doctors’ decisions about which ReSPECT conversations to prioritise and which to forgo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, we have previously reported that GPs view ReSPECT conversations as ongoing and processual. 19 However, excepting one doctor who encouraged the patient to take her time, the participating doctors aimed at completing the decision-making process in one conversation, timing conversations according to clinical urgency. In our earlier work on the full range of ReSPECT conversations – from those planned but not conducted, to those carried out to completion – we described how time constraints, coupled with clinical prompts such as a patient’s projected deterioration, influence doctors’ decisions about which ReSPECT conversations to prioritise and which to forgo.…”
Section: Discussionmentioning
confidence: 99%
“…, 17. , 19. In this analysis they employed a new focus – understanding incomplete conversations – and were alert to new themes.…”
Section: Methodsmentioning
confidence: 99%